2022
DOI: 10.1017/jfm.2022.732
|View full text |Cite
|
Sign up to set email alerts
|

Analytical model of fully developed wind farms in conventionally neutral atmospheric boundary layers

Abstract: The wind energy industry relies on computationally efficient engineering-type models to design wind farms. Typically these models do not account for the effect of atmospheric stratification in either the boundary layer or the free atmosphere. This study proposes a new analytical model for fully developed wind-turbine arrays in conventionally neutral atmospheric boundary layers frequently encountered in nature. The model captures the effect of the free-atmosphere stratification, Coriolis force, wind farm layout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Recent developments in this class of models include combining them with turbine wake models (Stevens, Gayme & Meneveau 2015, 2016 b ) or incorporating atmospheric (Emeis 2010; Abkar & Porté-Agel 2013; Peña & Rathmann 2014; Antonini & Caldeira 2021 a ; Li et al. 2022) and entrance effects (Meneveau 2012; Yang & Sotiropoulos 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent developments in this class of models include combining them with turbine wake models (Stevens, Gayme & Meneveau 2015, 2016 b ) or incorporating atmospheric (Emeis 2010; Abkar & Porté-Agel 2013; Peña & Rathmann 2014; Antonini & Caldeira 2021 a ; Li et al. 2022) and entrance effects (Meneveau 2012; Yang & Sotiropoulos 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Building on the above assumptions, a 'top-down' class of models has been devised, which assume that the wind farm acts as an additional roughness element (Frandsen 1992;Emeis & Frandsen 1993;Calaf et al 2010). Recent developments in this class of models include combining them with turbine wake models (Stevens, Gayme & Meneveau 2015, 2016b or incorporating atmospheric (Emeis 2010;Abkar & Porté-Agel 2013;Peña & Rathmann 2014;Antonini & Caldeira 2021a;Li et al 2022) and entrance effects (Meneveau 2012;Yang & Sotiropoulos 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Calaf, Meneveau & Meyers (2010) developed an improved top-down model by including an additional wake layer with enhanced turbulence levels. Later works have extended this approach to finite-length wind farms (Meneveau 2012), and included atmospheric stratification effects (Abkar & Porté-Agel 2013;Peña & Rathmann 2014;Sescu & Meneveau 2015;Li et al 2022). Although top-down models include the response of an idealised ABL to a large wind farm, this approach cannot account for layout effects.…”
Section: Introductionmentioning
confidence: 99%
“…Hezaveh et al [4] showed that "the wind-farm design with staggered-triangle clusters is the optimal design in terms of cost per unit power produced." Li et al [5] showed that the power output is higher in the staggered wind farms (horizontal-axis wind turbines) than in the aligned ones.…”
Section: Introductionmentioning
confidence: 99%